The spectrum of Lung and Pleural Neoplasms in Patients Presented to a Referral Hospital In Nepal - Mahat, Smritee; Karki, Shovana; Sayami, Gita (Journal of Karnali Academy of Health Sciences, 2022)
Background: Lung cancer is one of the most common cancers worldwide. Lung and pleural biopsies are the most commonly performed procedures for the diagnosis of suspicious lesions in the lungs and pleura. The main objective of the study was to identify the incidence pattern of lung and pleural neoplasms in the tertiary care center of Nepal.Methods: A hospital-based cross-sectional study was carried out from April 20, 2019, to April 19, 2020, taking the histopathological specimens with suspicion of lung or pleural neoplasms. Demographic data, type of biopsy obtained, laterality of involvement, smoking status, and histopathological diagnosis in lungs and pleura were collected in the pro forma and entered in Microsoft excel. The statistical analysis was done by using SPSS version 16.Results: Out of 7859 biopsies and resection specimens, 272 (3.5%) cases of lung and pleural specimens were obtained during the study period, out of which 101 (37.1%) were lung and 16 (5.9%) were pleural neoplasms altogether constituting 117 (43.01%) cases of the total lung and pleural biopsies. The mean age for lung and pleural neoplasms was 63.38 (SD±12.5) years. Male predominance was seen with M:E ratio of 1.6:1 and 1.3:1 in lung and pleural neoplasms respectively. Out of 117 cases, trucut biopsy was done for 104 (88.9%) cases and 62 (53%) cases specimens were obtained from the right side. Among the lung neoplasms, 87 (86.1%) were epithelial tumors among which 38 (43.7%) cases were Squamous cell carcinoma. Conclusion: Lung and pleural neoplasms were more prevalent in males in this study. Squamous cell carcinoma is the commonest histological type of lung cancer, closely followed by Adenocarcinoma in our study.